2022
DOI: 10.3389/fpubh.2022.790892
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Antimicrobial Resistance and Associated Factors Among Health Professionals at the University of Gondar Specialized Hospital: Institution-Based Cross-Sectional Study

Abstract: BackgroundAntimicrobial resistance is one of the many health challenges worldwide, particularly in resource-limited countries like Ethiopia. Increasing knowledge of health professionals can reduce the occurrence of antimicrobial resistance. In this study, we determined the antimicrobial resistance knowledge and examined the associated factors among the University of Gondar Hospital health professionals.MethodsAn institution-based cross-sectional survey was carried out. The samples were randomly recruited. Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…Two authors (BW, and MO) independently assessed the methodological quality of each study. In this manner, the following major components were evaluated for studies reporting descriptive cross-sectional data only [26,27]: Q1) Was the sample frame appropriate to address the target population? Q2) Were study participants sampled in an appropriate way?…”
Section: Methodological Quality (Risk Of Bias) Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Two authors (BW, and MO) independently assessed the methodological quality of each study. In this manner, the following major components were evaluated for studies reporting descriptive cross-sectional data only [26,27]: Q1) Was the sample frame appropriate to address the target population? Q2) Were study participants sampled in an appropriate way?…”
Section: Methodological Quality (Risk Of Bias) Assessmentmentioning
confidence: 99%
“…The sample size of the primary studies included in the review was significantly variable and ranged from (n = 91) [33] to (n = 571) [27]. Among the primary studies that reported gender [26][27][28][29][30][31][32][33][34][35][36][37][38], the majority of study participants (n = 2409) were male. All studies employed cross-sectional research designs [26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 On the other hand, a previous study reported that the higher knowledge among health professionals was associated with more working experience and fewer working hours. 51 Furthermore, the current study identified the associated factors with positive attitude, including, age, nationality and qualification. In Ethiopia, educational status and level of experience were associated with the attitude of the HCWs on hospital-acquired infection.…”
Section: Discussionmentioning
confidence: 98%
“…However, three hospitals still have not evaluated the AMR-CP team's ability to control antibiotic resistance in hospitals. Implementing an antibiotic stewardship program, leadership and management commitment, as well as the expertise of the team members, and an efective antimicrobial use policy helped to increase the rational use of antibiotics, decrease the prevalence of resistance, and provide signifcant economic benefts [32][33][34]. Terefore, AMR-CP should be supported and expanded so that antibiotics are used equally rationally throughout the hospital [35].…”
Section: Discussionmentioning
confidence: 99%